(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Alarge Number Of International Scholars agree thatEmperor ASOKA of India in the third century B.C. was one of the greatestconquerors who later achieved the most difficult conquest of all the conquestof himself through self-conviction and his perception of human suffering. Afterembracing the Dhamma of the Buddha as his guide and refuge, he transformed thegoal of his regime from military conquest to conquest by Dhamma. By providingroyal patronage for the propagation of Buddhism both within and outside hisvast dominion, he helped promote the metamorphosis of Buddhism from one amongmany sects of Indian ascetic spirituality into a world religion that waseventually to penetrate almost all of southern and eastern Asia. The presentcollection of papers by leading Indological scholars is intended to highlightdifferent aspects of the close connection between the political and religiouslife of this exemplary Indian ruler.